Taxonomy of the genus Brachyteles Spix, 1823 and its phylogenetic position within the subfamily Atelinae Gray, 1825 - Villavicencio, José Eduardo Serrano (2016)
Muriquis, genus Brachyteles Spix, 1823, are the largest of the extant New World primates, and they are one of the three extant genera of the subfamily Atelinae along with Ateles (spider monkeys) and Lagothrix (wooly monkeys). The taxonomy of Brachyteles has constantly changed since its first description in the 19th century. First treated as a monotypic genus, and after several modifications in the number of species, Brachyteles currently contains two species, B. arachnoides (Southern muriqui) and B. hypoxanthus (Northern muriqui). The morphological evidence for this taxonomic arrangement relies on two diagnostic characters: the occurrence of a black-pigmented face and the absence of the first digit (thumb) in Southern muriqui populations vs. mottled face and fully-developed thumb in Northern muriqui populations. In addition, the phylogenetic relationship between atelines is disputed: on the one hand, the molecular evidence suggests an (Ateles (Brachyteles + Lagothrix)) clade and, on the other, most morphological evidence supports a clade (Lagothrix (Ateles + Brachyteles)) based on the high degree of postcranial and locomotory resemblances between Ateles and Brachyteles. My aims here are: 1) to verify how many taxa at the species level group there are in Brachyteles, and 2) to estimate the phylogenetic relationships among Atelinae using morphological characters. To achieve these goals, I have performed a qualitative analysis of external morphological characters as the presence or absence of the thumb, pelage coloration, and face pigmentation to test sexual dimorphism or dichromatism and intrapopulational variation. I also performed linear and geometric morphometrics analyses to test sexual dimorphism and geographical variation in both size and shape of the skull. Finally, I carried out a morphological phylogeny using 74 discrete morphological characters, two ecological and one karyological. This analysis includes 11 species of extant and fossil atelids and the outgroup was composed of Sapajus nigritus and Callicebus personatus. The analysis of the pelage coloration reveals that there is no sexual dimorphism or dichromatism in Brachyteles; besides, the pelage presents a high degree of individual variation. The development of the thumb and the facial pigmentation do not exhibit uniformity; thus, they have no taxonomic meaning. Linear and geometric morphometrics failed on to discriminate between sexes and populations based on the size and shape of the skull. For these reasons, I consider Brachyteles as a monotypic genus with no subspecies. Lastly, the morphologic phylogenetic analysis shows that Brachyteles is more closely related to Lagothrix than to Ateles, suggesting that the postcranial similarities between muriquis and spider monkeys could be a plesiomorphic condition in Atelidae, and the arboreal quadrupedalism of Alouatta and Lagothrix evolved convergently in alouattines and atelines.